Implementasi Opsi Jumbo Packet Header Ipv6 pada Ethernet Jumbo Frame - Putu Ade Arta Kusuma Putra Suparta; Primantara Hari Trisnawan; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The use of IPv4 in addressing causes problems with the growing number of internet users. IPv6 is designed to overcome the weaknesses of IPv4. This study uses the IPv6 Extension Header feature to accommodate larger packet shipments than ordinary IPv6 packets. UDP is a protocol used in streaming applications that allows efficient packet transfer of resources. Large UDP packet delivery requires a large throughput, because the size of the package sent is large. Throughput is the number of packets that can be sent and received within a certain period from source to destination. The solution to sending packets that have sizes over 1500 bytes is to increase throughput by creating a new header option on IPv6 that is able to accommodate payload sizes that exceed 1500 bytes to 9000 bytes. Also can utilize Ethernet jumbo frames (up to 9000 bytes) that currently using ethernet frames, to reduce network overhead. As a result, the new header implemented as the IPv6 jumbo packet header is successfully run on the NS-3 simulator and can send packets over 1500 bytes to less than 9000 bytes as many as 100 packets on a jumbo ethernet frame network. So it can reduce the overhead header.